The The Influence of Social Environment and Income on Motivation to Play Online Gambling (Slot) in Medan Helvetia District - Dimas Ardiansyah; Ahmad Perdana Indra; Tuti Anggraini (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Gambling is the act of consciously risking something in a game with expected risks and rewards. Online gambling is done by utilizing a digital platform to place bets using real money. In Indonesia, the most popular online gambling is slots. This study aims to identify whether there is an influence of social environment and income on the motivation to play online gambling (slots) in Medan Helvetia District. Quantitative research methods were used in this study with data collection conducted through questionnaires. The data collected was analyzed and processed using the IBM SPSS Statistics 30.0.0 application. The results showed that the social environment has a positive and significant effect on the motivation to play online gambling (slots), where someone who is in an environment that has been involved in online gambling tends to have greater motivation to play online gambling. Meanwhile, income also has a positive and significant effect, someone with a low income playing online gambling is more motivated by economic factors, while those with high income tend to play because of entertainment